Active textile: woven-cloth-like mechanisms consist of thin McKibben actuators. (3rd April 2023) - Hiramitsu, Tatsuhiro; Suzumori, Koichi; Nabae, Hiroyuki; Endo, Gen
ABSTRACT: Pneumatic artificial muscles have some advantages. Especially, the flexibility of artificial muscles contributes to compose novel mechanisms. Authors succeeded in manufacturing novel soft mechanisms that are composed of only woven artificial muscles and strings. We called this mechanism active textile. The structure is uniformed with woven artificial muscles; nevertheless, the forms and movements of mechanisms are diverse. We aim to establish a design method for these active textiles. We reported that deformations of active textiles are changed by woven structures. In addition to that, wefts' characteristics such as cross-sectional shape, bending stiffness and elasticity determine the characteristic of a textile. Deformations of active textiles are caused by the contraction and the expansion of thin McKibben muscles. In this paper, authors focus on the contraction and curvature deformation of the active textile due to the drive of the artificial muscles.We fabricated active textiles with different wefts and different weave structures.Contraction and bending deformations of active textiles in the warp and weft directions are assumed geometrically. In addition, we verified the validity by experiments. GRAPHICAL ABSTRACT: UF0001